Differentiation of human glioblastoma U87 cells into cholinergic neuron. (21st June 2019) - Liu, Honghui; Xia, Jinye; Wang, Tiansheng; Li, Wei; Song, Yexun; Tan, Guolin
Highlights: The glioblastoma cell line U87 can be differentiated into cholinergic neuron characteristics. Sodium butyrate can induce the U87 cells differentiation into cells with cholinergic neuron characteristics. Akt participates in the process of U87 cell differentiation into cholinergic neuron characteristics. Abstract: To facilitate research methodologies for investigating the role of cholinergic nerves in many diseases, establishing an in vitro cholinergic neuron model is necessary. In this study, we investigated whether human glioblastoma U87 cells could be differentiated into cholinergic neurons in vitro. Sodium butyrate was used as the differentiation agent. The differentiated cells established by inducing U87 cells with sodium butyrate were named D-U87 cells. Immunofluorescence was used to label the neuronal markers MAP2, NF-M, and ChAT and the glial marker GFAP in D-U87 cells. Flow cytometry was used to measure cell cycle distribution in D-U87 cells. PCR, protein chip, and western blot assays were used to measure the expression levels of muscarinic cholinergic receptor 1 (M1), M4, ChAT, SYP and Akt. ELISA was used to measure neurotransmitter levels. As a result, we found that sodium butyrate induced U87 cell differentiation into cells with neuronal characteristics and increased not only the expression levels of the cholinergic neuron-related proteins M1, M4, ChAT and SYP in D-U87 cells but also the acetylcholine neurotransmitters in D-U87 cells. Moreover, the Akt protein expression in D-U87 cells was increased compared with that in U87 cells. Finally, we found that M1, M4, ChAT and SYP protein expression and acetylcholine secretion levels were significantly decreased in D-U87 cells after treatment with the Akt inhibitor MK-2206. These results demonstrate that D-U87 cells exhibit cholinergic neuron characteristics and that sodium butyrate induced U87 cell differentiation into cholinergic neuron partially through Akt signaling.